2013
DOI: 10.1159/000354519
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin Reduces Gap Junction Mediated Cell-to-Cell Communication in Proximal Tubule-Derived Epithelial Cells

Abstract: Background/Aims: In the current study we examined if the adipocytokine, visfatin, alters connexin-mediated intercellular communication in proximal tubule-derived epithelial cells. Methods: The effects of visfatin (10-200ng/mL) on cell viability and cytotoxicity in HK2-cells were assessed by MTT, crystal violet and lactate dehydrogenase assays. Western blot analysis was used to confirm expression of Cx26, Cx40 and Cx43. The effect of visfatin (10-200ng/mL) on TGF-β1 secretion was confirmed by ELISA, and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Having confirmed that in both acute and chronic time points, glucose/TGF-β1 evoked changes in CX expression are paralleled by reduced GJIC, we wanted to determine if hemi-channel activity increased as a compensatory mechanism to maintain cell-to-cell communication. Carboxyfluorescein is a membrane impermeant dye that has been previously used to assess hemi-channel opening in a variety of cell types [31]. An increase in carbenoxleone-sensitive dye uptake suggested that the number and/or activity of hemi-channels was elevated in cells cultured in TGF-β1 for 48h and 7days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having confirmed that in both acute and chronic time points, glucose/TGF-β1 evoked changes in CX expression are paralleled by reduced GJIC, we wanted to determine if hemi-channel activity increased as a compensatory mechanism to maintain cell-to-cell communication. Carboxyfluorescein is a membrane impermeant dye that has been previously used to assess hemi-channel opening in a variety of cell types [31]. An increase in carbenoxleone-sensitive dye uptake suggested that the number and/or activity of hemi-channels was elevated in cells cultured in TGF-β1 for 48h and 7days.…”
Section: Discussionmentioning
confidence: 99%
“…Described previously [31], cells cultured on glass cover-slips were transferred to the recording bath and perfused (2ml/min) with physiological saline solution composed of (mM): 127 NaCl, 1.9 KCl, 1.2 KH 2 PO 4 , 26 NaHCO 3 , 1 MgCl 2 , 2CaCl 2 and 10 D-Glucose bubbled with 95% O 2 / 5 % CO 2 and maintained at 32°C. Cells were visualized (x600 magnification) using IR-DIC optics (Olympus BX51W1 microscope and Hitachi CCD camera).…”
Section: Methodsmentioning
confidence: 99%
“…ZO-1 and N-cadherin) and have been shown to be downregulated in podocytes, endothelial cells, and tubular cells in vitro , in diabetic mouse models, and human DN [ 64 ]. Interestingly, it has been found that visfatin, an adipokine that is elevated in patients with type 2 diabetes, inhibits the expression of CX43 in proximal tubular cells, illustrating the intricacy involved in understanding the in vivo situation of diabetic patients [ 65 ].…”
Section: In Vitro Evidence For Emt and Endomt Omentioning
confidence: 99%
“…Different types of junctions, which connect cells to their microenvironment, are part of a communication network essential for signaling. The loss of cell-cell adhesion can be associated with a subsequent reduction of gap junctions or with local changes in the environment and these changes can then activate ion-related receptors in neighboring cells [5]. Such events demonstrate that different stimuli can have vastly different effects.…”
Section: Introductionmentioning
confidence: 99%